Bioinformatics analysis of structure and function of Lebestatine isolated from Macrovipera venom - Maryam Rabiee; Hossein Sazgar; Farzaneh Mohammadi Farsani (Fasa University of Medical Sciences, 2017)
Background & Objective: Lebestatin is a new member of disintegrin family. This single-chain poly peptide comprises 107 amino acids isolated from Macrovipera venom. Lebestatin is connected to integrin, counteracts the adhesion and emigration of endothelial cells through inhibiting the action of this protein and has anti-vessel formation effect. The goal of this study was to survey the interaction of this peptide with integrin and identify important amino acids involved in this interaction. Material & methods: Given the importance of Lebestatin in inhibiting the adhesion and migration of cancer cells, in this study the structure of this peptide was constructed through Phyre2 server and it was compared with other similar peptides. In the next step, in order to identify the mechanisms of the action of this peptide, its interaction with integrin α1 subunit was investigated with Z-Dock server. The results of this interaction were analyzed with Chimera 1.5.3 and SPDBV. Results: The results obtained from simulation showed that the structure of Lebestatin is closely similar to its co-family proteins. Moreover, bioinformatics studies showed that Lys50, Cys71 and Thy92 residues of Lebestatin and Asp20, Tyr17, His118 of integrin α1 subunit are significant amino acids involved in the interaction between Lebestatin and its target integrin. Conclusion: Bioinformatics studies applied in this investigation resulted in identifying significant amino acids involved in the interaction between Lebestatin and its target integrin. Results of this study could facilitate the development of more effective peptides for the inhibition of integrin, metastasis and angiogenesis of cancer cells.